The Islamic Entries in Three Major English Dictionaries - Abdurrosyid Abdurrosyid (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2017)
The study is to analyze Islamic entries in three major English dictionaries; Oxford Dictionary of English (ODE), Merriam-Webster’s Advanced Learners’Dictionary (MWALED), and Macquarie Australian National Dictionary (MAND). The three dictionaries are used the object of this study because they represent the major varieties of English besides the existence of a great number of new Englishness emerges around the globe. The selected entries are in accordance to Islamic sciences such as theology, Islamic Jurisprudence, Quranic exegesis, hadith Science, Islamic mysticism and Islamic History. Inappropriate and inaccurate or misleading definitions given by the dictionaries are identified and analyzed, then they will be examined according to definitions from each Islamic science so that accurate and appropriate definitions can be delivered as the alternatives and in turn more acceptable definitions and understandings of Islam will be given to not only the Muslim communities but also the greater readers.DOI: 10.15408/insaniyat.v2i1.6588